2022
DOI: 10.3390/v14020188
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins as Regulators of Internal Initiation of Viral mRNA Translation

Abstract: Viruses are obligate intracellular parasites that depend on the host’s protein synthesis machinery for translating their mRNAs. The viral mRNA (vRNA) competes with the host mRNA to recruit the translational machinery, including ribosomes, tRNAs, and the limited eukaryotic translation initiation factor (eIFs) pool. Many viruses utilize non-canonical strategies such as targeting host eIFs and RNA elements known as internal ribosome entry sites (IRESs) to reprogram cellular gene expression, ensuring preferential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 441 publications
(946 reference statements)
0
13
0
Order By: Relevance
“…These strategies are in part facilitated by the delocalization of RBPs to the cytoplasm in infected cells, an event that increases the pool of functionally active factors for viral RNA translation. Soon after the discovery of picornavirus IRES elements in 1988 [5,6], it was found that full IRES activity required the action of host factors, as exemplified by the polypyrimidine tract‐binding protein (PTB), poly(rC)‐binding protein 2 (PCBP2), ErbB3‐binding protein 1 (Ebp1, also known as ITAF 45 and PA2G4), or the cold‐shock domain containing E1 (CSDE1, also known as Unr), among others [50–54], reviewed in [38,55].…”
Section: Host Factors Involved In Picornavirus Rna Translationmentioning
confidence: 99%
See 4 more Smart Citations
“…These strategies are in part facilitated by the delocalization of RBPs to the cytoplasm in infected cells, an event that increases the pool of functionally active factors for viral RNA translation. Soon after the discovery of picornavirus IRES elements in 1988 [5,6], it was found that full IRES activity required the action of host factors, as exemplified by the polypyrimidine tract‐binding protein (PTB), poly(rC)‐binding protein 2 (PCBP2), ErbB3‐binding protein 1 (Ebp1, also known as ITAF 45 and PA2G4), or the cold‐shock domain containing E1 (CSDE1, also known as Unr), among others [50–54], reviewed in [38,55].…”
Section: Host Factors Involved In Picornavirus Rna Translationmentioning
confidence: 99%
“…Hence, the first phase of the picornavirus infection cycle requires the translation of the viral RNA, which is governed by the IRES element. This property is shared with other RNA viruses, such as hepatitis C (HCV), a member of the Flaviviridae family, as well as members of the families Dicistroviridae (CrPV) and Retroviridae (HIV-1), reinforcing the fact that the use of IRES elements represents an optimized strategy for achieving successful viral infection [37,38]. A key feature of viral IRES elements is that they are active outside of its natural RNA background, promoting cap-independent activity in different genetic contexts.…”
Section: Picornavirus Translation Strategies For Evading Shutdown Of ...mentioning
confidence: 99%
See 3 more Smart Citations